المرأة والممارسة الصحفية في الجزائر: نحو تأنيث المهنة؟ - فدول, محمد (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2022)
نتناول هنا مسألة مهمة تتعلق بظاهرة جديدة في قطاع الإعلام في الجزائر والمتمثلة في ظاهرة تأنيث مهنة الصحافة. وبالرغم من النقص المسجل في الدراسات السوسيوغرافية والسوسيولوجية التي اهتمت بالنساء الصحفيات، إلا أن تلك المنجزة حول الصحفيين بصفة عامة تؤكد على أن نسبة النساء الصحفيات في تزايد مستمر، خاصة في مجال السمعي البصري، أين نجد عدد النساء الصحفيات أكبر من عدد الرجال الصحفيين في الكثير من المؤسسات التابعة لهذا القطاع المهم. وبالتالي، حاولنا في تحليلنا هذا فهم هذه الظاهرة و تحليل بعض السمات الشخصية والمهنية المهمة مثل: المستوى التعليمي، التخصص العلمي، السن والأقدمية في الممارسة المهنية لهذه الفئة المهنية، والتي تسمح لنا تحديد البروفيل السوسيومهني للنساء الصحفيات. Abstract: Here we address an important issue related to a new phenomenon in the media sector in Algeria, which is the phenomenon of the feminization of the profession of journalism. Despite the recorded shortage in sociogrqfical and sociological studies that focused on women journalists, those conducted about journalists in general confirm that the percentage of women journalists is constantly increasing, especially in the audiovisual field. Thus, we tried in our analysis to understand this phenomenon and analyze some important personal and professional characteristics: educational level, scientific specialization, age and seniority in the professional practice of this professional category.